TARTARUGAS MARINHAS E FIBROPAPILOMATOSE: UM ESTUDO CIENCIOMÉTRICO NO BRASIL: Sea turtles and fibropapilomatosis: a scienciometric study in Brazil - Souza Azevedo, Juliana; Nonato Guimarães, Priscilla Aparecida (Arquivos de Ciências do Mar, 2023)
Fibropapillomatosis (FP) is a viral disease that affects sea turtles worldwide, affecting their vital functions. The aim of this study was to perform a scientometric analysis of studies on sea turtles in Brazil, focusing on FP. Although Brazil ranks third in the world in terms of studies on PF in sea turtles, there is still a lack of publications on this disease, which is not a central topic in marine turtle research, with about 16% of the global publication on FP. Chelonia mydas is the most studied species for FP, with a predominance of studies on the subject in the states of São Paulo, Espírito Santo, Rio de Janeiro, Bahia e Ceará. In terms of financial support, most of the studies are supported by national grants. In addition, the authorship leadership from 2000 to 2021 was made up of men, until 2017, with an increase of women researchers publishing in the field from 2018. The importance of maintaining and providing funding and resources for studies on PF in Brazil is observed, with the measuring the impact of the disease. Furthermore, it is important to increase the contribution of women researchers contribution in science and studies with more conservation actions to marine turtles and their natural habitat, in order to contribute to the monitoring of the health of the marine ecosystem and habitats close to the Brazilian coast. Keywords: sea turtles, conservation, fibropapillomatosis, scientometrics, literature review.